Comparison of virus concentration methods for the reverse-transcriptase quantitative PCR (RT-qPCR)-based detection of bacteriophage Φ6, an enveloped virus surrogate for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA, from untreated wastewater at St. George's University (SGU), Grenada. (28th October 2021) - Farmer-Diaz, K; Matthew-Bernard, M; Ramos-Nino, M; Fitzpatrick, D; Cheetham, S
Abstract: Introduction/Objective: With the ongoing coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the consequent opening of borders, it is of paramount importance to monitor communities for the presence of potential COVID-19 clusters. Wastewater-based epidemiology (WBE) is an effective way to monitor community spread of pathogens and has been implemented in many countries to identify potential outbreaks. Most standardized methodologies used in WBE for the detection of viruses have been validated for non-enveloped viruses; therefore, there is a need for the creation of a standardized method for the detection of enveloped viruses, such as SARS-CoV-2. Methods/Case Report: Wastewater seeded with a Pseudomonas syringae bacteriophage (Φ6) was used to test the efficiency of five wastewater virus concentration methods. Two methods were based on AlCl3 flocculation with different pH adjustments. The other methods utilized membrane filtration followed by beef elution: one added a pretreatment with HCl; another added a pretreatment with MgCl2; and finally, an untreated control. A known amount of Bacteriophage Φ6 was used for all methods, and detection was quantified by reverse-transcription quantitative polymerase chain reaction. Results (if a Case Study enter NA): The Cq values for each method, ranging from 24.38–38.6, were compared. The highest recovery of Φ6 was obtained with the AlCl3 flocculation method with an adjusted pH of 6, followed in descending order by MgCl2-pretreated sample with beef elution; HCl-pretreated sample with beef elution, the untreated sample, and AlCl3 flocculation method with an adjusted pH of 3.5. Conclusion: The results suggest that AlCl3 flocculation with an adjusted pH of 6 may be a quick and cost-effective methodology for the detection of enveloped viruses in WBE. This can facilitate the implementation of WBE at SGU, Grenada, as a useful tool to conduct active surveillance and track outbreaks of enveloped viral diseases, such as SARS-CoV-2.